Ways of Learning to Teach A Philosophically Inspired Analysis of Teacher Education Programs - Back, Shlomo. (SensePublishers : Imprint: SensePublishers, 2012)
This book deals with commonly reported accusations about the nature of teacher education based on arguments and disagreements about what teacher education should do, how it should do it and what it should produce in its graduates. Much of these accusations are on out of date or obsolete ideals of the "good" teacher. It is a philosophical exploration of the crisis in which teacher education finds itself in the world of neo-liberal capitalism, privatization, accountability, consumerism and globalization. The book develops a meta-theory of teacher education which analyses three major approaches to teacher education (Enlightenment, Romanticism, and Belief-Oriented programs), each of them suggest a different epistemological and ethical world-view. Accordingly, each of them lead to a different vision of teachers' identity, and inform different type of programs of teacher education. While critically discussing how each of the three approaches is manifested in various Teacher Education programs, the book proposes a new synthesis arising from them. Although seemingly contradictory, they can be seen as various aspects of a more "balanced", multifaceted and adequate ideal of a better way to prepare teachers in the present era. Ways of Learning to Teach is a tribute to the work of teacher educators and is informing for anyone who is interested in teaching and learning in the 21st century. This is a compelling book that brings together a number of conflicting (and often taken-for-granted) views of teacher preparation in ways that helps to makes sense of the complex enterprise that is teacher education. Back offers an interesting and thought provoking way of understanding criticisms about teacher education and offers a positive and productive way forward. This book is a must read for teacher educators.